Fundacion Jalisco Incubator : Mexico Case Study - World Bank (World Bank, Washington, DC, 2014)
After hearing of the success of Fundacion Chile, the governor of the Mexican state of Jalisco sought to recreate the foundation locally. The result is Fundacion Jalisco, which seeks to import successful business models to small farmers in Jalisco. For its first project, the Fundacion imported high-yield blueberry plants from the United States, started a nursery, and gave the plants to local farmers who were capable of growing them successfully. The farmers deliver their berry harvest to the foundation, which packages and sells it throughout Mexico and overseas in the United States and the United Kingdom. The venture has been highly profitable for all concerned, and the foundation is now seeking to diversify into value-added products such as olive oil and cheese. The foundation relies on a combination of state funding and private investment.